Effect of different feeds on larval development and survival of ornamental koi carp, Cyprinus carpio (Linnaeus, 1758) larvae in laboratory condition (Journal of the Bangladesh Agricultural University, 2012)
The experiment was conducted for 56-day with a view to observe the effects of different feeds on larval development  and survival of 3 day-old ornamental koi carp Cyprinus carpio larvae in fiber glass aquaria to develop rearing technique for promoting its aquaculture and for promoting the aquarium business. There were three treatments, each  having two replications, stocked with 30 larvae having an initial length and weight of 2.31 ± 0.10 mm and weight of  0.005 ± 0.01 g respectively, in a glass aquaria of size 30 × 10 × 6 inch3. Three different feeds i.e. crushed pellet feed, mixed diet i.e. 50% pellet + 50% chopped tubificid worms and live chopped tubificid worms, having different protein  levels were administered to compare their suitability as food for the rearing of C. carpio larvae. The larvae fed with chopped tubificid worms showed significantly better results in terms of length and weight gain, percent length and weight gain and specific growth rate (SGR %) compared to the rest two treatments. The highest survival rate 56.66 ± 2.29% was shown by the chopped tubificid worms fed larvae which was significantly higher than those of crushed pellet feed and mixed diet respectively. Water quality parameters were monitored throughout the experimental periods. On the basis of larval development and survival rate, it could be suggested the live chopped tubificid worms is suitable for the culture of ornamental koi carp C. carpio larvae.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12112   J. Bangladesh Agril. Univ. 10(1): 179183, 2012